Motivation of Parents Visit and Educational Value for Children Aged 5-6 Years at Tourist Object Kura-Kura Ocean Park Jepara - Zahro, Masfiyyatuz; Waluyo, Edi (BELIA: Early Childhood Education Papers, 2018)
This study aims to determine the motivation that influences the willingness of visitors (parents) to visit their children and the value of education on the attractions of Kura-kura Ocean Park Jepara (KOP). This study uses a qualitative research approach with a descriptive study. The subjects of this study were visitors (parents and children aged 5-6 years) as the main informants, managers as supporting informants while the representatives of HIMPAUDI as triangulation informants. The selection of informants used purposive sampling technique. The methods and techniques of data collection in this research are interviews, observation, and document analysis. The data analysis technique in this study is the interactive data analysis of Miles & Huberman. The results showed that parents visiting KOP attractions were influenced by several internal factors including boredom with daily activities, finding new experiences (educating children), utilizing leisure time to be with family (looking for togetherness ) Meanwhile, the pull factor (external) among them is the KOP tourist attraction has a unique building / beauty of the attractions offered, road access to attractions is very easy, and the facilities and infrastructure offered are only in KOP attractions. There is a value of religious education, that is, children trust God through His creation, but the value of religious education in terms of worship has not been obtained by the child. The value of social education includes children interacting directly with friends, relatives, parents or teachers. Moral education values ​​include children being taught to queue, not littering, sharing provisions, not disturbing fish or turtles, loving animals and being taught to respect the older. Cultural education values ​​include the KOP tourist attraction is an icon of Jepara, KOP is located on the beach which is one of the characteristics of coastal areas, other local wisdom is wood carving or craft.